The total synthesis of the annonaceous acetogenin, muricatetrocin C. - Dixon, D; Ley, S; Reynolds, D (2002)
The total synthesis of the potential antitumour agent muricatetrocin C has provided an ideal stage for the exploitation and development of new chemistry. A convergent synthetic strategy has been realised incorporating three distinct pieces of methodology, these include a highly diastereoselective hetero-Diels-Alder reaction to construct the butenolide terminus, an oxygen to carbon rearrangement to install the trans-2,5-disubstituted tetrahydrofuran ring and a spatial desymmetrisation process to afford the anti-diol unit.